"An Affair on Uncertain Ground": Sarah Kirsch's Poetry Volume Erlking 's Daughter in the Context of Her Prose After the Wende - Christine Cosentino (Studies in 20th & 21st Century Literature, 1997)
Translated by James Rolleston. Sarah Kirsch, who in the wake of the Biermann scandal moved from East to West Germany in 1977, is arguably the most talented living German lyric poet. But she is also a prose writer. It seems that since her break with the GDR in 1977 and the breakup of the GDR in 1989, this particular genre has gained importance in her literary output. Her diary-like prose records and blends intense reactions to events of change or collapse, "German brouhaha": political, historical, environmental, existential, and personal. Critics have called Kirsch's prose "lyrical prose" and her latest poetry "more prosaic," "feeling its way in close proximity to prose." The prose volumes Chaff (1991), Vibrating Turf (1991), and The Simple Life (1994), as well as her poems in the volume Erlking's Daughter (1992), increasingly evoke the impression of "scattered notes," of "fleetingness," deliberate vagueness, or a "calculated lack of structure" in times that are still "unstructured and without character." Political events, environmental changes, relationships, structures and strivings of whatever kind are marked by the suggestive sign of a meaningless, threatening "affair on uncertain ground." The thought of formlessness, of the formal destructuring of prose and poetry suggests Kirsch's uncertainty and pessimism about the possibility of artistically and philosophically restructuring or controlling reality.
Keywords: Translated; James Rolleston; Sarah Kirsch; Biermann scandal; East to West; East Germany; West Germany; 1977; German lyric poet; GDR; DDR; 1989; poetry; prose; diary-like prose; German brouhaha; German; Germany; political; historical; environmental; existential; personal; lyrical prose; prosaic; Chaff; Vibrating Turf; The Simple Life; Erlking' s Daughter; scattered notes; fleetingness; structure; lack of structure; Political events; environmental changes; relationships; structures; striving; formlessness; destructuring of prose; destructuring of poetry; uncertainty; pessimism; artistically; philosophically